A N, O co-doped hierarchical carbon cathode for high-performance Zn-ion hybrid supercapacitors with enhanced pseudocapacitance. Issue 23 (2nd June 2020) - Deng, Xiaoyang; Li, Jiajun; Shan, Zhu; Sha, Junwei; Ma, Liying; Zhao, Naiqin
Abstract : A novel carbon cathode was fabricated for high-performance Zn-ion supercapacitors with enhanced pseudocapacitance. Abstract : Zn-ion hybrid supercapacitors (ZHSs) are an advanced energy storage system with high energy/power density. However, the development of cathodes with high-performance is still a challenge. Herein, N, O co-doped hierarchical porous carbon (HPC) integrated with carbon cloth (CC) was fabricated as a promising cathode for aqueous ZHSs, which delivered a high specific capacity of 138.5 mA h g −1 with excellent rate performance ( 75 mA h g −1 at 20 A g −1 ) and superb cycling stability without decay after 10 000 cycles. As a result, an exceptionally high energy density of 110 W h kg −1 and attractive power density of 20 kW kg −1 can be obtained. More importantly, the dual cation (H + and Zn 2+ ) chemical absorption process for additional capacity is firstly proposed and verified by ex situ experiments, while the precipitation/dissolution process of zinc hydroxide sulphate hydrate is explained. Furthermore, a quasi-solid-state HPC/CC-based ZHS device based on gel electrolyte also showed promising potential for practical applications. This work provides a new pathway to develop carbon-based cathode materials for sustainable ZHSs.